Translation and validation of the Brazilian version of the Cerebral Palsy Quality of Life Questionnaire for Children - Child report - Braccialli, Lígia M.P. [UNESP]; Almeida, Vanessa S. [UNESP]; Sankako, Andreia N. [UNESP]; Silva, Michelle Z. [UNESP]; Braccialli, Ana C. [UNESP]; Carvalho, Sebastião M.R. [UNESP]; Magalhães, Alessandra T. (Elsevier, 2016)
Objective To verify the psychometric properties of the Cerebral Palsy: Quality of Life Questionnaire Children - child report (CPQol-Child) questionnaire, after it was translated and culturally adapted into Brazilian Portuguese. Methods After the translation and cultural adaptation of the tool into Brazilian Portuguese, the questionnaire was answered by 65 children with cerebral palsy, aged 9-12 years. The intraclass correlation coefficient and Cronbach's alpha were used to assess the reliability and internal consistency of the tool and its validity was analyzed through the association between CPQol-Child: self-report tool and Kidscreen-10 using Pearson's correlation coefficient. Results Internal consistency ranged from 0.6579 to 0.8861, the intraobserver reliability from 0.405 to 0.894, and the interobserver from 0.537 to 0.937. There was a weak correlation between the participation domain and physical health of CPQol-Child: self-report tool and Kidscreen-10. Conclusion The analysis suggests that the tool has psychometric acceptability for the Brazilian population.
Keywords: Cerebral palsy; Child; Quality of life